Isolation of biofilm forming Bacillus strains and their antibacterial activity - Huy, Nguyen Quang; Hang, Tran Thuy (Academia Journal of Biology, 2012)
Biofilms are densely packed multicellular communities of microorganisms attached to a surface or interface. Microorganisms live in a biofilm as the dense and protected environment of the film that allow them to cooperate and interact in various ways. While many make biofilm microbes are harmful, species of the genus Bacillus are useful. From soil samples, water contaminated and mud collected in the different locations in Hanoi, Vietnam, we have isolated several microorganisms including bacteria, fungi, actinomyces. Among them two different strains U1.3 and U3.7 are more active in biofilm formation than others based on the violet crystalline method. The data from measurement of absorbability at 570 nm wave length showed U1.3 and U3.7 have higher value (0.95 and 0.89, respectively) compare to others strains (0.58). Based on morphological, biological characteristics and sequences of 16 S rDNA, the two isolated strains were classified as Bacillus. The U1.3 and U3.7 strains are similar to Bacillus subtilis (AB042061) and Bacillus velezensis (AY603658) at 99.9% and 99.5% respectively. Both strains U1.3 and U3.7 were well grown at 37oC and pH from 6.5 to 7.5. Especially strain U3.7 could grow in temperatures above 50oC. Both strains can use different nitrogen and carbon sources for growth and biofilm forming. The data from agar diffusion method showed both strains inhibited the growth of pathogenic microorganisms, such as, Phytophthora sp., E. coli or Ralstonia sp.. This is the first research results on the strains of the genus Bacillus that can simultaneously generate biofilm and inhibit the growth of bacteria in Vietnam. The further studies on the biofilm formation and optimum conditions for the efficiency in biocontrol of two Bacillus strains are needed.